Monitoring and management on insect pest of oil palm at Ladang UiTM Jasin / Nur Natassha Zahid Anuar - Zahid Anuar, Nur Natassha (Faculty of Plantation and Agrotechnology, 2018)
Worldwide, there are many pests infested in oil palm plantation that will affect the growth and yield of oil palm production. The majority of this pest are leaf feeder and can cause damage by defoliating the oil palm. Monitoring insect pests and damage assessment will help Unit Ladang UiTM Jasin on the choosing the proper management for the crop and decrease the number of the pest. The objectives of this study are to identify insect pest of Oil Palm at Ladang UiTM Jasin and to determine effective controls method on insect population of Oil Palm at Ladang UiTM Jasin. This study were done for four (4) weeks, from January until February 2018 at the 80 immatured oil palm. The trap were setup randomly at the plot by using Yellow Sticky Trap. Data of insect pest were recorded once every 5 days for four weeks, and the data was collected in the early of the morning (between 7 to 9 am). Three different treatment was applied are chemical control, cultural control and combination of chemical and cultural control and with no treatment as control plot. Experimental design used in this study was completely randomized design to reduce a bias from the results. The result indicate six (6) major insect pests found with the order Hymenoptera is the highest number found at Oil palm in Ladang UiTM Jasin. In addition, the effective treatment for insect pests at oil palm is chemical and cultural compared with other treatment tested. These result will help Unit Ladang on the einformation of insect pest at oil palm areas and the proper management to be implement.